Thermally conductive sheet and method for producing a thermally conductive sheet

CN106457801BActive Publication Date: 2026-10-30SEKISUI CHEMICAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN201580017182.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2014-03-31
Filing Date
2015-02-13
Publication Date
2026-10-30
Estimated Expiration
2035-02-13

AI Technical Summary

Technical Problem

因此,有必要对PET膜进行底涂处理,导致工序数增加

Benefits of technology

根据本发明,由于含有聚乙烯醇缩醛树脂和苯乙烯-乙烯基异戊二烯嵌段共聚物的支撑树脂层与丙烯酸类树脂层的丙烯酸单体交联,因此可提高丙烯酸类树脂层与支撑片的密合性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN106457801B_ABST
    Figure CN106457801B_ABST
Patent Text Reader

Abstract

The present invention provides a thermally conductive sheet having excellent adhesion between an acrylic resin layer and a support sheet, and a method for producing the same. The thermally conductive sheet has: a thermally conductive resin layer (11) formed from an acrylic thermally conductive composition; and a support resin layer (support sheet) (12) containing a polyvinyl acetal resin and a styrene-vinyl isoprene block copolymer. Since the support sheet is crosslinked with an acrylic monomer of the acrylic thermally conductive resin layer, the adhesion between the thermally conductive resin layer and the support sheet can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an acrylic thermally conductive sheet for heat dissipation measures in electronic components and the like, and a method for preparing the thermally conductive sheet. This application claims priority to Japanese Patent Application No. 2014-74776, filed on March 31, 2014, which is incorporated herein by reference. Background Technology

[0002] In recent years, thermally conductive sheets have been used as heat dissipation measures for electronic components (see, for example, Patent Document 1). In thermally conductive sheets, a thermally conductive resin layer with excellent flexibility is sometimes used to improve the fit with electronic components. However, this highly flexible thermally conductive resin layer may stretch or break during use, making it difficult to handle. Therefore, support sheets that reinforce the thermally conductive resin layer are used.

[0003] However, when using a support sheet, such as a PET film, the acrylic thermally conductive resin layer can be easily peeled off. Therefore, it is necessary to perform a primer coating on the PET film, resulting in an increase in the number of processing steps.

[0004] Existing technical documents Patent documents Patent document 1: Japanese Patent Application Publication No. 2007-123624. Summary of the Invention

[0005] The problem that the invention aims to solve In view of the above-mentioned existing situation, the present invention provides a thermally conductive sheet with excellent adhesion between the acrylic resin layer and the support sheet, and a method for preparing the same.

[0006] Methods for solving problems The inventors conducted in-depth research and discovered that by using a support sheet containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer, the adhesion between the acrylic resin layer and the support sheet can be improved.

[0007] That is, the thermally conductive sheet of the present invention is characterized by having: a thermally conductive resin layer formed of an acrylic thermally conductive composition; and a supporting resin layer containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer.

[0008] In addition, the support sheet of the present invention is characterized by containing: polyvinyl acetal resin and styrene-vinyl isoprene block copolymer.

[0009] Furthermore, the method for preparing the thermally conductive sheet of the present invention is characterized by comprising the following steps: mixing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer, sheeting the mixture to form a supporting resin layer; and curing an acrylic thermally conductive composition in contact with the supporting resin layer to form a thermally conductive resin layer.

[0010] In addition, the method for preparing the support sheet of the present invention is characterized by: mixing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer and then forming it into a sheet.

[0011] Invention Effects According to the present invention, since the supporting resin layer containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer is crosslinked with the acrylic monomer of the acrylic resin layer, the adhesion between the acrylic resin layer and the supporting sheet can be improved. Attached Figure Description

[0012] [ Figure 1 ] Figure 1 This is a cross-sectional view showing an example of a thermally conductive sheet according to one embodiment of the present invention.

[0013] [ Figure 2 ] Figure 2 This is an explanatory diagram of the method for determining the T-type peel strength between the thermally conductive resin layer and the supporting resin layer. Detailed Implementation

[0014] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings and in the following order.

[0015] 1. Thermally conductive sheet 2. Preparation method of thermally conductive sheet 3. Example <1. Thermally conductive sheet> One embodiment of the thermally conductive sheet of the present invention comprises: a thermally conductive resin layer formed of an acrylic thermally conductive composition; and a supporting resin layer containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer. The preferred thickness of the thermally conductive sheet is 0.1 mm or more and 10.0 mm or less, and the preferred thickness of the supporting resin layer is 0.001 mm or more and 0.500 mm or less.

[0016] Figure 1 This is a cross-sectional view showing an example of a thermally conductive sheet according to one embodiment of the present invention. The thermally conductive sheet includes: a thermally conductive resin layer 11 formed by curing an acrylic thermally conductive composition; and a supporting resin layer 12 supporting the thermally conductive resin layer 11. Furthermore, a release film 13, which is peeled off during use, is attached to the surface of the thermally conductive resin layer 11.

[0017] The thermally conductive resin layer 11 is a layer obtained by curing an acrylic thermally conductive composition. The preferred thermal conductivity of the thermally conductive resin layer 11 is 0.3 W / m·K or higher. Furthermore, the load capacity of the thermally conductive resin layer 11 is 1 kgf / cm². 2 The preferred compression ratio is 1% or more and 80% or less. The higher the compression ratio, the better the flexibility, and the better the fit for the heating or cooling element. In addition, the preferred Asker C hardness (JISK 7312) of the thermally conductive resin layer 11 is 5 or more and 60 or less.

[0018] As an acrylic thermally conductive composition, conventionally known acrylic thermally conductive compositions can be used. Examples include acrylic thermally conductive compositions containing (A) monofunctional (meth)acrylates, (B) polyfunctional (meth)acrylates, (C) photopolymerization initiators, (D) thermally conductive particles, (E) plasticizers, and (F) thiol compounds.

[0019] As a monofunctional (meth)acrylate, an alkyl (meth)acrylate having a straight-chain or branched alkyl group is preferred. Examples of alkyl (meth)acrylates include: methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and (meth)acrylate. Isooctyl acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate, isomyrmethyl (meth)acrylate, n-tetrazyl (meth)acrylate, n-tetradecyl (meth)acrylate, n-octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, n-lauryl (meth)acrylate, etc., may be used in one or more of these.

[0020] Examples of multifunctional (meth)acrylates include: 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. Bifunctional (meth)acrylates such as (meth)acrylates; trifunctional or higher (meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, di-trimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate may be used, one or more of these may be used.

[0021] Examples of photopolymerization initiators include: benzophenones, benzoin derivatives, benzoin alkyl ethers, and benzoyl dimethyl ketals. α α-hydroxy ketones, acylphosphine oxides, etc., one or more of these can be used.

[0022] Examples of thermally conductive particles include: metal hydroxides such as aluminum hydroxide and magnesium hydroxide; metals such as aluminum, copper, and silver; metal oxides such as aluminum oxide and magnesium oxide; nitrides such as aluminum nitride, boron nitride, and silicon nitride; and carbon nanotubes. One or more of these can be used.

[0023] Regarding the content of thermally conductive particles in the acrylic thermally conductive composition, it is 100 parts by mass or more and 2000 parts by mass, preferably 300 parts by mass or more and 650 parts by mass or less, relative to 100 parts by mass of monofunctional (meth)acrylate. If the content of thermally conductive particles is too low, the thermal conductivity of the thermally conductive sheet will be difficult to improve sufficiently; if the content of thermally conductive particles is too high, the flexibility of the thermally conductive sheet tends to decrease. In addition, when using two thermally conductive fillers with different average particle sizes, the blending ratio of small-diameter filler to large-diameter filler is preferably 15:85 to 90:10.

[0024] As a plasticizer, for example, at least one selected from the following can be used: adipate, pimecrolate, octanoate, azelaate, sebacic acid ester. Such dicarboxylic acid esters can be obtained by esterifying a dicarboxylic acid selected from HOOC-(CH2)4-COOH, pimecrolate, octanoic acid, azelaic acid, or sebacic acid with an alcohol by conventional methods. More specifically, at least one selected from the following is preferred: diisodecyl adipate, diisodecyl pimecrolate, diisodecyl octanoate, diisodecyl azelaate, or diisodecyl sebacic acid obtained by esterifying one of HOOC-(CH2)4-COOH, pimecrolate, octanoic acid, azelaic acid, or sebacic acid with isodecanol.

[0025] As thiols, multifunctional thiols with difunctionality or higher are used. Examples of multifunctional thiols with difunctionality or higher include: 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2-methyl-2-((3-mercapto-1-oxopropyl)-methyl)propane-1,3-dimethylbis(3-mercaptopropionate), trimethylolpropane trithiopropionate, trimethylolpropane trithioethylene glycol, 2,4,6-trimercapto-S-triazine, etc.; tetrafunctional thiols such as pentaerythritol tetra(3-mercaptobutyrate), pentaerythritol tetrathioglycolate, dipentaerythritol tetrathioglycolate, pentaerythritol tetrathiopropionate, etc.; pentafunctional thiols such as dipentaerythritol pentathioglycolate; and hexafunctional thiols such as dipentaerythritol hexathioglycolate, etc. One or more of these compounds may be used.

[0026] In addition, antioxidants, heat aging inhibitors, flame retardants, colorants, etc., can be mixed into acrylic thermally conductive compositions as other components.

[0027] Examples of antioxidants include primary antioxidants that capture free radicals generated by thermal aging and secondary antioxidants that decompose peroxides generated by thermal aging. These can be used alone or in combination. Examples of agents that prevent thermal aging include monoacrylate of 1,1-bis(2-hydroxy-3,5-di-tert-amylphenyl)methane.

[0028] Furthermore, regarding acrylic thermally conductive compositions, the above-described composition is not the only limitation; other acrylic thermally conductive compositions may also be used. Examples of commercially available products include: TransCool GNS series (INOACCORPORATION Co., Ltd.), Shirokinon series (Taica Co., Ltd.), and 5580H (Sumitomo 3M Co., Ltd.).

[0029] The supporting resin layer 12 is a support sheet containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer.

[0030] Polyvinyl alcohol acetal resin is a resin obtained by acetalizing polyvinyl alcohol with an aldehyde. Polyvinyl alcohol can be obtained, for example, by saponifying polyvinyl acetate, with a saponification degree typically between 80 mol% and 99.8 mol%. Furthermore, the degree of polymerization of polyvinyl alcohol is typically between 200 and 3000. Examples of aldehydes include formaldehyde, acetaldehyde, n-butyraldehyde, isobutyraldehyde, n-hexanaldehyde, and n-pentanaldehyde; one or more of these can be used. Polyvinyl alcohol acetal or polyvinyl alcohol butyraldehyde, obtained by reacting acetaldehyde or butyraldehyde with polyvinyl alcohol, is particularly suitable.

[0031] The molecular weight of polyvinyl alcohol acetal resin is 5 × 10⁻⁶. 4 Above and 20×10 4 The following is more preferably 8×10 4 Above and 15×10 4 The following applies: If the molecular weight is too low, it will exhibit stickiness, and the dryness of the support sheet may be reduced; if the molecular weight is too high, the flexibility of the support sheet may be reduced.

[0032] In addition, the glass transition temperature (Tg) of polyvinyl acetal resin is 50°C or higher and 150°C or lower, more preferably 80°C or higher and 120°C or lower. If the glass transition temperature is too low, it will exhibit stickiness, and the dryness of the support sheet may be reduced; if the glass transition temperature is too high, the flexibility of the support sheet may be reduced.

[0033] Furthermore, the degree of acetalization of the polyvinyl alcohol acetal resin (or the degree of butyralization when it is polyvinyl butyral resin) is 50 mol% or more and 90 mol% or less, more preferably 60 mol% or more and 80 mol% or less. If the acetalization is too low, the compatibility with the styrene-vinyl isoprene block copolymer may decrease; if the acetalization is too high, the heat resistance of the support sheet may decrease.

[0034] The degree of acetalization is a percentage value obtained by dividing the amount of vinyl groups bonded by the acetal groups by the total amount of vinyl groups in the main chain. The degree of acetalization can be calculated as follows: using the method based on JIS K6728 "Test Method for Polyvinyl Butyral", the degree of acetylation (amount of acetyl groups) and the content of hydroxyl groups (amount of vinyl alcohol) are determined. The mole fraction is calculated based on the results, and then the degree of acetylation and the content of hydroxyl groups are subtracted from 100 mol%.

[0035] Commercially available products of such polyvinyl acetal resins include, for example, S-LEC BX-1, BX-5, KS-3, and KS-5 (Sekisui Chemicals Co., Ltd.).

[0036] Styrene-vinyl isoprene block copolymers are triblock copolymers composed of styrene blocks and vinyl-polyisoprene blocks. They are thermoplastic elastomers in which styrene units are the hard segments and vinyl isoprene units are the soft segments.

[0037] The styrene-vinyl isoprene block copolymer has a styrene content of 10% or more and 30% or less, preferably 15% or more and 25% or less. If the styrene content is too low, the hard segments will be insufficient, and the elasticity of the rubber may be reduced; if the styrene content is too high, the flexibility of the support sheet may be reduced.

[0038] Furthermore, the glass transition temperature (Tg) of the styrene-vinyl isoprene block copolymer is above -40°C and below +40°C, preferably above -20°C and below +20°C. If the glass transition temperature is too low, it will exhibit stickiness, and the dryness of the support sheet may be reduced; if the glass transition temperature is too high, the flexibility of the support sheet may be reduced.

[0039] Commercially available examples of such styrene-vinyl isoprene block copolymers include, for example, HYBRAR 5125 and 5127 (Kuraray Co., Ltd.).

[0040] Furthermore, it is preferable to blend polyvinyl acetal and styrene-vinyl isoprene block copolymer in a mass ratio of 9:1 to 7:3. If the amount of styrene-vinyl isoprene block copolymer is too small, it will not be able to achieve good adhesion with the thermally conductive resin layer; if the amount of styrene-vinyl isoprene block copolymer is too large, it may lead to a decrease in the dryness or strength of the support sheet.

[0041] In addition, a crosslinking agent may be added to the supporting resin layer 12. Examples of crosslinking agents include isocyanate crosslinking agents, epoxy crosslinking agents, and silicone crosslinking agents; one or more of these may be used.

[0042] Furthermore, it is preferable that the surface of the supporting resin layer 12 is rough. By roughening the surface of the supporting resin layer 12, the surface area in contact with the thermally conductive resin is increased, thereby increasing the crosslinking points of the vinyl group, and thus improving the adhesion through the fixation effect.

[0043] As the release film 13, for example, a film formed by coating a release agent such as silicone onto PET (Polyethylene Terephthalate), OPP (Oriented Polypropylene), PMP (Poly-4-methylpentene-1), PTFE (Polytetrafluoroethylene), etc. can be used.

[0044] According to this type of thermally conductive sheet, the adhesion between the thermally conductive resin layer and the support sheet is improved because the supporting resin layer containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer is cross-linked with the acrylic monomers of the acrylic thermally conductive resin layer. Furthermore, the surface of the support sheet is dry, thus improving operability. Additionally, due to the excellent thermal conductivity and flexibility of the thermally conductive sheet, it is suitable for use in precision instruments such as hard disk drives and laser devices.

[0045] It should be noted that, in the above embodiments, although a configuration is formed in which a supporting resin layer is provided on one side of the thermally conductive resin layer, it is also possible to form a configuration in which a supporting resin layer is provided on both sides of the thermally conductive resin layer, or vice versa. Furthermore, in the above embodiments, the support sheet is applied to the thermally conductive sheet, but this is not a limitation. For example, the support sheet can be used as a support material for acrylic adhesive tapes or bonding tapes.

[0046] <2. Preparation method of thermally conductive sheet> A method for preparing a thermally conductive sheet according to one embodiment of the present invention includes the following steps: mixing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer, sheeting the mixture to form a supporting resin layer; and curing an acrylic thermally conductive composition in contact with the supporting resin layer to form a thermally conductive resin layer.

[0047] In the process of forming the supporting resin layer, a styrene-vinyl isoprene block copolymer is added and mixed into a polyvinyl acetal resin to prepare a supporting resin composition, wherein the styrene-vinyl isoprene block copolymer is present in an amount of 10 parts by weight or more and 65 parts by weight or less, preferably 10 parts by weight or more and 45 parts by weight or less, relative to 100 parts by weight of the polyvinyl acetal resin. Sheet formation can be performed as follows: for example, the supporting resin composition is uniformly coated onto a release film using a doctor blade coater and then dried. Since both the polyvinyl acetal resin and the styrene-vinyl isoprene block copolymer are thermoplastic resins, sheet formation can be performed solvent-free using methods such as spray molding, extrusion molding, or compounding.

[0048] In the process of forming the thermally conductive resin layer, the acrylic thermally conductive composition is cured while in contact with the supporting resin layer. It is believed that this allows the vinyl portion of the styrene-vinyl isoprene block copolymer in the supporting resin layer and the acrylic monomer portion of the acrylic thermally conductive composition to become miscible or cured, thereby forming an integrated structure and improving adhesion. Conventional curing methods such as light, heat, and solvents can be used, but at least one of light or heat is preferred.

[0049] In addition, during the process of forming the thermally conductive resin layer, the acrylic thermally conductive composition can be cured while being held between two support sheets, or the acrylic thermally conductive composition can be cured while being coated on both sides of the support sheets.

[0050] According to this method of preparing a thermally conductive sheet, in the process of forming the thermally conductive resin layer, the thermally conductive resin layer and the supporting resin layer can be firmly bonded by curing the acrylic thermally conductive composition. Example

[0051] <3. Examples> The embodiments of the present invention will now be described. In this embodiment, polyvinyl acetal and styrene-vinyl isoprene block copolymer were mixed in a specified mass ratio to form a supporting resin layer. Next, a thermally conductive resin layer obtained by curing an acrylic thermally conductive composition was formed on the supporting resin layer to produce a thermally conductive sheet. Then, for each thermally conductive sheet, the tensile strength, the T-peel strength between the supporting resin layer and the thermally conductive resin layer, and the surface tack of the supporting resin layer were measured and evaluated. It should be noted that the present invention is not limited to these embodiments.

[0052] The fabrication, tensile strength determination and evaluation, T-peel strength determination and evaluation, and surface adhesion determination and evaluation of the thermally conductive sheet are carried out as follows.

[0053] [Making of thermally conductive sheets] A supporting resin composition was obtained by mixing polyvinyl acetal (S-LEC BX-1, Sekisui Chemicals Co., Ltd.) and styrene-vinyl isoprene block copolymer (HYBRAR 5125, Kuraray Co., Ltd.) in a specified mass ratio. The supporting resin composition was then coated onto a release film made of PET using a doctor blade coater, forming a supporting resin layer with a thickness of 0.01 mm.

[0054] An acrylic thermally conductive composition was prepared by mixing 100 parts by weight of 2-ethylhexyl acrylate as a monofunctional acrylate, 47 parts by weight of castor oil-derived fatty acid ester as a plasticizer, 1.5 parts by weight of neopentyl glycol diacrylate hydroxypentanoic acid (KAYARADFM-400, Nippon Kayaku Co., Ltd.) as a polyfunctional acrylate, 1.4 parts by weight of photopolymerization initiator (IRGACURE 819, BASF Co., Ltd.), 400 parts by weight of aluminum hydroxide powder (average particle size 80 μm) and 400 parts by weight of aluminum hydroxide powder (average particle size 8 μm) as thermally conductive fillers.

[0055] An acrylic thermally conductive composition is coated onto a supporting resin layer, and the coating is applied at a rate of 1 mW / cm from both the acrylic thermally conductive composition surface and the supporting resin surface. 2 The irradiation intensity was simultaneously irradiated with ultraviolet light for 5 minutes, forming a thermally conductive resin layer on the supporting resin layer, thus creating a thermally conductive sheet composed of a supporting resin layer with a thickness of 0.01 mm and a thermally conductive resin layer with a thickness of 1.0 mm.

[0056] [Determination and Evaluation of Tensile Strength] A thermally conductive sheet consisting of a thermally conductive resin layer 11 and a supporting resin layer 12 was fabricated using a punch (dumbbell-shaped No. 3) with a minimum width of 5 mm and a minimum length of 20 mm, and processed using a manual press. The specimen was then subjected to tensile testing using a tensile testing machine (RTG-1225, Orientec) at a speed of 500 mm / min, and the strength at break (fracture) was determined (the tensile load value was divided by the cross-sectional area of ​​the specimen). Specimens with a tensile strength of 0.4 MPa or higher were rated "○", and specimens with a tensile strength less than 0.4 MPa were rated "×".

[0057] [Determination and Evaluation of T-Peel Strength] Using a tensile testing machine (RTG-1225, Orientec), such as Figure 2 As shown, a release film 13A made of PET is bonded to the thermally conductive resin layer 11, and a release film 13B made of PET is bonded to the supporting resin layer 12. In this state, the interlayer peel strength between the thermally conductive resin layer 11 and the supporting resin layer 12 is determined by a T-type peel test. The tensile speed is 300 mm / min and the sample width is 15 mm. Samples with an interlayer peel strength of 0.2 N / 20 mm or more are rated as "○", samples with a peel strength of less than 0.2 N / 20 mm but more than 0.15 N / 20 mm are rated as "△", and samples with a peel strength of less than 0.15 N / 20 mm are rated as "×".

[0058] [Measurement and Evaluation of Surface Adhesion] As a viscosity testing machine, the TAC-II viscosity testing machine manufactured by RHESCA was used. A 10mm diameter aluminum cylindrical probe was pressed onto the supporting resin layer under the following conditions: pressing speed 30mm / min, peeling speed 120mm / min, load 196g, pressing time 5.0 seconds, tensile distance 5mm, and probe not heated. The probe viscosity upon peeling was then measured. The viscosity of the supporting resin layer was less than 10kN / m. 2 The sample was evaluated as "○" and 10 kN / m 2 Above but less than 15kN / m 2 The sample was evaluated as "△" and 15 kN / m 2 The above samples are rated as "×".

[0059] <Comparative Example 1> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-vinyl isoprene block copolymer in a mass ratio of 10:0, a thermally conductive sheet was prepared as described above. As shown in Table 1, the tensile strength of Comparative Example 1 was rated as ○, the T-peel strength as ×, and the surface tack as ○.

[0060] <Example 1> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-vinyl isoprene block copolymer in a 9:1 mass ratio, a thermally conductive sheet was fabricated as described above. As shown in Table 1, the tensile strength of Example 1 was rated as ○, the T-peel strength as △, and the surface tack as ○.

[0061] <Example 2> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-vinyl isoprene block copolymer in a mass ratio of 8.5:1.5, a thermally conductive sheet was fabricated as described above. As shown in Table 1, the tensile strength, T-peel strength, and surface tack of Example 2 were rated as ○, ○, and ○, respectively.

[0062] <Example 3> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-vinyl isoprene block copolymer in a mass ratio of 8:2, a thermally conductive sheet was fabricated as described above. As shown in Table 1, the tensile strength, T-peel strength, and surface tack of Example 3 were rated as ○.

[0063] <Example 4> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-vinyl isoprene block copolymer in a 7:3 mass ratio, a thermally conductive sheet was fabricated as described above. As shown in Table 1, the tensile strength of Example 4 was rated as ○, the T-peel strength as ○, and the surface tack as △.

[0064] <Comparative Example 2> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-vinyl isoprene block copolymer at a mass ratio of 0:10, a thermally conductive sheet was prepared as described above. As shown in Table 1, the tensile strength of Comparative Example 2 was rated as ×, the T-peel strength as ○, and the surface tack as ×.

[0065] <Comparative Example 3> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-ethylene / butene-styrene block copolymer (SEPTON V9827, Kuraray Co., Ltd.) in a 9:1 mass ratio, a thermally conductive sheet was prepared as described above. As shown in Table 1, the tensile strength of Comparative Example 3 was rated as ○, the T-peel strength as ×, and the surface tack as ○.

[0066] <Comparative Example 4> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-ethylene / butene-styrene block copolymer (SEPTON V9827, Kuraray Co., Ltd.) in a 7:3 mass ratio, a thermally conductive sheet was prepared as described above. As shown in Table 1, the tensile strength of Comparative Example 4 was rated as ○, the T-peel strength as ×, and the surface tack as ○.

[0067] <Comparative Example 5> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-ethylene / butene-styrene block copolymer (SEPTON V9827, Kuraray Co., Ltd.) in a 3:7 mass ratio, a thermally conductive sheet was prepared as described above. As shown in Table 1, the tensile strength, T-peel strength, and surface tack of Comparative Example 5 were rated as ×, ×, and ×, respectively.

[0068] <Comparative Example 6> Except for forming a supporting resin layer by mixing polyvinyl acetal and styrene-ethylene / butene-styrene block copolymer (SEPTON V9827, Kuraray Co., Ltd.) at a mass ratio of 0:10, a thermally conductive sheet was prepared as described above. As shown in Table 1, the tensile strength, T-peel strength, and surface tack of Comparative Example 6 were rated as ×, ×, and ×, respectively.

[0069] [Table 1] As shown in Comparative Examples 3-6, when a styrene-ethylene / butene-styrene block copolymer without unsaturated bonds is added, the interlayer peel strength between the thermally conductive resin layer and the supporting resin layer is low, and excellent adhesion cannot be obtained. Furthermore, as shown in Comparative Example 1, when the supporting resin layer is formed solely of polyvinyl acetal, the interlayer peel strength between the thermally conductive resin layer and the supporting resin layer is low, and excellent adhesion cannot be obtained. Additionally, as shown in Comparative Example 2, when the supporting resin layer is formed solely of a styrene-vinyl isoprene block copolymer, the tensile strength of the thermally conductive sheet decreases, and the supporting resin layer exhibits stickiness, resulting in reduced drying performance.

[0070] On the other hand, as shown in Examples 1-4, when polyvinyl acetal and styrene-vinyl isoprene block copolymer are mixed in a mass ratio of 9:1 to 7:3 to form a supporting resin layer, the interlayer peel strength between the thermally conductive resin layer and the supporting resin layer is high, resulting in excellent adhesion. Furthermore, the thermally conductive sheet also exhibits high tensile strength and maintains the dryness of the supporting resin layer.

[0071] Symbol Explanation 11 Thermally conductive resin layer, 12 Supporting resin layer, 13 Release film

Claims

1. A thermally conductive sheet, which has the following characteristics: A thermally conductive resin layer formed from an acrylic thermally conductive composition; and, A supporting resin layer containing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer. The above-mentioned polyvinyl acetal resin and the above-mentioned styrene-vinyl isoprene block copolymer are blended in a mass ratio of 9:1 to 7:

3.

2. The thermally conductive sheet according to claim 1, wherein, The aforementioned polyvinyl acetal resin is either polyvinyl acetal or polyvinyl butyral.

3. The thermally conductive sheet according to claim 1 or 2, wherein, The molecular weight of the above-mentioned polyvinyl acetal resin is 5 × 10⁻⁶. 4 Above and 20×10 4 the following.

4. The thermally conductive sheet according to claim 1 or 2, wherein, The glass transition temperature of the above-mentioned polyvinyl acetal resin is above 50°C and below 150°C.

5. The thermally conductive sheet according to claim 3, wherein, The glass transition temperature of the above-mentioned polyvinyl acetal resin is above 50°C and below 150°C.

6. The thermally conductive sheet according to claim 1 or 2, wherein, The styrene content of the above-mentioned styrene-vinyl isoprene block copolymer is more than 10% and less than 30%.

7. The thermally conductive sheet according to claim 3, wherein, The styrene content of the above-mentioned styrene-vinyl isoprene block copolymer is more than 10% and less than 30%.

8. The thermally conductive sheet according to claim 4, wherein, The styrene content of the above-mentioned styrene-vinyl isoprene block copolymer is more than 10% and less than 30%.

9. The thermally conductive sheet according to claim 5, wherein, The styrene content of the above-mentioned styrene-vinyl isoprene block copolymer is more than 10% and less than 30%.

10. The thermally conductive sheet according to claim 1 or 2, wherein, The glass transition temperature of the above-mentioned styrene-vinyl isoprene block copolymer is above -40°C and below +40°C.

11. The thermally conductive sheet according to claim 3, wherein, The glass transition temperature of the above-mentioned styrene-vinyl isoprene block copolymer is above -40°C and below +40°C.

12. The thermally conductive sheet according to claim 4, wherein, The glass transition temperature of the above-mentioned styrene-vinyl isoprene block copolymer is above -40°C and below +40°C.

13. The thermally conductive sheet according to claim 5, wherein, The glass transition temperature of the above-mentioned styrene-vinyl isoprene block copolymer is above -40°C and below +40°C.

14. The thermally conductive sheet according to claim 6, wherein, The glass transition temperature of the above-mentioned styrene-vinyl isoprene block copolymer is above -40°C and below +40°C.

15. A support sheet comprising polyvinyl acetal resin and styrene-vinyl isoprene block copolymer, wherein the polyvinyl acetal resin and the styrene-vinyl isoprene block copolymer are blended in a mass ratio of 9:1 to 7:3, and the support sheet exhibits a viscosity of less than 15 kN / m in a probe viscosity test. 2 .

16. A method for preparing a thermally conductive sheet, comprising the following steps: The process of mixing polyvinyl acetal resin and styrene-vinyl isoprene block copolymer, sheeting them together, and forming a supporting resin layer; and... The process of curing an acrylic thermally conductive composition in contact with the above-mentioned supporting resin layer to form a thermally conductive resin layer.

17. A method for preparing a support sheet, wherein the support sheet has a viscosity of less than 15 kN / m in a probe viscosity test. 2 The support sheet, among which, Polyvinyl acetal resin and styrene-vinyl isoprene block copolymer were mixed in a mass ratio of 9:1 to 7:3 and then sheeted.

Citation Information

Patent Citations

  • Manufacturing method of heat conduction sheet and heat conduction sheet manufactured thereby

    JP2007123624A

  • Cleaning device, process cartridge, and image forming apparatus

    JP2014074776A

  • Heat radiating member and connection structure

    CN100339983C

  • Thermal conductive sheet

    JP2008042168A

  • Heat conductive sheet and heat dissipation plate

    JP2012158695A